APPLICATION OF SELF ASSEMBLY REMEMBRANCE ASMAWIYAH SAVINGS (TQN) - Abdul Hoir; Yuce Yuliana, SKom, MM (Jurnal Sistem Informasi, 2000)
With existence of computerized system of service is expected to be faster in dealing with accessing savings and saving searches, compared with the manual method. Information and reports on concrete, such as weekly reports, savings reports, and lists of depositors. Data storage and computation of the total savings can be implemented quickly with the help of computer media, the software Visual Basic 5.0